Analysis Strategy Blended Learning of Prospective Islamic Teacher After Covid 19 Pandemic - Supardi Ritonga; Zuhri Zuhri; Muhammad Aufa Muis; Nur Rahmatillah; Euis Nur Istiqomah; Nina Zakiah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Students as prospective Islamic teachers are required to be able to create learning strategies that arouse student motivation, such as blended learning strategies. The purpose of this study was to analyze the effect of the blended learning method on the motivation of prospective Islamic teachers. and the use of e-learning media on the motivation of prospective Islamic teacher students. The population in this study were students of the Islamic religious education study program at STAIN Bengkalis. This type of research is quantitative. The sampling technique used was purposive sampling, the requirements for the sampling of this research were students who took part in the PAI learning strategy lectures in 2021. The number of samples used was 77 students. The questionnaire was used as a data collection technique for this research. Hypothesis testing utilizes the T test and the determinant coefficient R2. The results of this study obtained a tcount of 3.66, which is greater than tÂ¬table of 3.202 with a confidence level of 99%. It can be concluded that blended learning-based learning has a significant effect on the learning motivation of prospective Islamic religious teachers at STAIN Bengkalis. Through the test results of the R2 determinant coefficient of 0.58, it can be concluded that the blended learning strategy can affect students' learning motivation by 58%. This is because students' interest in blended learning strategies triggers students' curiosity to explore Islamic religious education learning strategies.